Domain size manipulation of perflouorinated polymer electrolytes by sulfonic acid-functionalized MWCNTs to enhance fuel cell performance - Kannan, Ramaiyan; Parthasarathy, Meera; Maraveedu, Sreekuttan U.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Langmuir, 2009)
The application of sulfonic acid-functionalized multiwalled (s-MWNT) carbon nanotubes to manipulate the hydrophilic domain size of Nafion membranes is explored here as an option for tuning the proton conductivity of polymer electrolyte membranes for hydrogen-oxygen fuel cells. The electrochemical impedance experiments provide preliminary evidence of increased proton conductivity, while small-angle X-ray scattering measurements line. out enhanced ionic cluster domain size in these composite membranes as the central reason for higher conductivity (70 angstrom for the optimum composite membrane vs 50 angstrom for Nafion 115) values. Scanning electrochemical microscopy indicates synergistic interaction between the sulfonic acid functional groups present in the Nation membrane and those on the nanotube surface. More interestingly, the nanotube-tailored Nafion membranes ameliorate the performance of fuel cells as confirmed by measurements at a sin le-cell level, which reveal a maximum power density of 380 mW cm(-2), higher than those of Nafion 115 (250 mW cm(-2)) and recast Nafion (230 mW cm-2) membranes. Thus, in addition to providing an elegant means of controlling the ionic cluster size, the strategic approach of using CNT both as an anchoring backbone for -SO(3)H groups to enrich proton conductivity and as a blending agent to improve the mechanical characteristics of the Nafion phase might be helpful in alleviating many critical problems associated with the use of commercial Nafion membranes.